Topsoil organic carbon mineralization and CO2 evolution of three paddy soils from South China and the temperature dependence - ZHANG, Xu-hui; LI, Lian-qing; PAN, Gen-xing (Journal of environmental sciences (China), 2007)
Carbon mineralization and its response to climatic warming have been receiving global attention for the last decade. Although the virtual influence of temperature effect is still in great debate, little is known on the mineralization of organic carbon （SOC） of paddy soils of China under warming. SOC mineralization of three major types of China＇s paddy soils is studied through laboratory incubation for 114 d under soil moisture regime of 70% water holding capacity at 20℃ and 25℃ respectively. The carbon that mineralized as CO2 evolved was measured every day in the first 32 d and every two days in the following days. Carbon mineralized during the 114 d incubation ranged from 3.51 to 9.22 mg CO2-C/gC at 20℃ and from 4.24 to 11.35 mg CO2-C/gC at 25℃ respectively; and a mineralizable C pool in the range of 0.24 to 0.59 gC/kg, varying with different soils. The whole course of C mineralization in the 114 d incubation could be divided into three stages of varying rates, representing the three subpools of the total mineralizable C： very actively mineralized C at 1-23 d, actively tnineralized C at 24--74 d and a slowly mineralized pool with low and more or less stabilized C mineralization rate at 75-114 d. The calculated Q10 values ranged from 1.0 to 2.4, varying with the soil types and N status. Neither the total SOC pool nor the labile C pool could account for the total mineralization potential of the soils studied, despite a well correlation of labile C with the shortly and actively mineralized C, which were shown in sensitive response to soil warming. However, the portion of microbial C pool and the soil C/N ratio controlled the C mineralization and the temperature dependence. Therefore, C sequestration may not result in an increase of C mineralization proportionally. The relative control of C bioavailability and microbial metabolic activity on C mineralization with respect to stabilization of sequestered C in the paddy soils of China is to be further studied.